The predictive value of optic nerve sheath diameter measurement via ultrasound for intracerebral hemorrhage complicated by cerebral-cardiac syndrome - Wei-Ze Fan; Jun-Rong Jiang; Hui-Ling Zang; Hui Cheng; Xiao-Hui Shen; Wen-Juan Yang; Hui Wang; Li-Xing Jing (BMC Neurology)
Abstract Objective This study aims to evaluate the clinical significance of ultrasound-based measurement of optic nerve sheath diameter (ONSD) in predicting intracerebral hemorrhage (ICH) complicated by cerebral-cardiac syndrome (CCS). Methods Patients with ICH and who were treated in the intensive care unit (ICU) at Shijiazhuang People’s Hospital between October 2021 and November 2022 were included in this study. Participants were divided into two groups: those with CCS and those without. Various clinical parameters, including sex, age, electrocardiogram (ECG) findings, myocardial markers, B-type natriuretic peptide (BNP) levels, Glasgow Coma Scale (GCS) score, ONSD, hematoma volume, and midline shift, were assessed. A binary logistic regression model and receiver operating characteristic (ROC) curve analysis were employed to determine the predictive value of each risk factor for ICH complicated by CCS. Results ONSD measurements differed significantly between males and females, with males exhibiting larger ONSD values. Additionally, significant differences were observed in ONSD, hematoma volume, midline shift, and GCS scores between the CCS and non-CCS groups. A direct correlation was identified between ONSD and both hematoma volume and midline shift. Multiple regression analysis demonstrated that ONSD, hematoma volume, and GCS score are independent risk factors for predicting ICH complicated by CCS. ROC curve analysis for ONSD in predicting ICH with CCS revealed an area under the curve (AUC) of 0.80, with an optimal cutoff value of 5.88 cm, yielding a sensitivity of 83% and a specificity of 79%. When ONSD, hematoma volume, and GCS score were combined, the predictive accuracy improved, with an AUC of 0.880. Conclusion Males tend to have larger ONSD measurements compared to females. Ultrasound is a valuable tool for measuring ONSD, comparable to computed tomography, and is useful in detecting intracranial hypertension and mass effect. ONSD, hematoma volume, and GCS score are independent predictors of ICH complicated by CCS, and their combined use enhances predictive accuracy.